Descontinuidades, controvérsias e significação das políticas públicas educacionais no Brasil: estudo de caso “Programa Mais Educação” - Almeida, Alessandra Felix de (2017)
The current dissertation took as a case study the “Programa Mais Educação” (More Education Program), with the goal of discussing the relationship between the phases of Formulation and of Implementation of Public Policies, based on the idea of Policy Cycle. The study considered the history of Integral Education in Brazil, the role of teachers in the educational process, the development of teaching in the Brazilian scenario, the elements of Policy Management and the Brazilian political-social history, all as relevant data for the Policy Analysis. The case studied was affected by the political conjuncture in 2016, which was marked by the approval of the Impeachment process and the respective loss of Dilma Rousseff's presidential term, resulting, among other changes in the governmental agenda, in the extinction of the Program in question. This is highlighted in this work, as it reveals the complexity of the Policy Analysis, as well as the fragility of Social Policies